2016
DOI: 10.1259/bjr.20150868
|View full text |Cite
|
Sign up to set email alerts
|

Communicating radiation risk to patients and referring physicians in the emergency department setting

Abstract: Heightened awareness about the radiation risks associated with CT imaging has increased patients' wishes to be informed of these risks, and has motivated efforts to reduce radiation dose and eliminate unnecessary imaging. However, many ordering providers, including emergency physicians, are ill prepared to have an informed discussion with patients about the cancer risks related to medical imaging. Radiologists, who generally have greater training in radiation biology and the risks of radiation, often do not ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…26,31 It could be hypothesized that this communication gap may partly result from a heavy workload in radiological departments, often making it difficult for the radiological staff to provide patients with exhaustive information about radiation exposure. Several studies have highlighted patients' preference to speak directly with imaging experts about their imaging findings, 19,[32][33][34][35] further emphasizing the need for improved direct communication between radiological staff and patients.…”
Section: Jama Network Open | Imagingmentioning
confidence: 99%
“…26,31 It could be hypothesized that this communication gap may partly result from a heavy workload in radiological departments, often making it difficult for the radiological staff to provide patients with exhaustive information about radiation exposure. Several studies have highlighted patients' preference to speak directly with imaging experts about their imaging findings, 19,[32][33][34][35] further emphasizing the need for improved direct communication between radiological staff and patients.…”
Section: Jama Network Open | Imagingmentioning
confidence: 99%
“…For instance, in emergency medicine, a physician has limited knowledge of a patients’ medical history as well as limited time and would be more inclined to choose radiological imaging. 51 When a patient is provided with a choice between “observation” and CT, the patient tendency is to avoid the radiation. 22 However, taking the CT is likely more cost-effective and ethical, for example, for nontraumatic, nonspecific abdominal pain, since it has been shown that a substantial proportion of these patients will continue to suffer, 52,53 even 5-years later.…”
Section: Resistance Of Patients/parents To Receive Radiological Examsmentioning
confidence: 99%
“…16,21 Lack of an understanding of radiation risks jeopardizes effective risk/benefit discussions and undermines the decision process for ordering the CT. 19,21 Studies show that sharing radiation risk information between providers and patients occurs seldomly (<25% cases). 10,16,21,22,25,26 Despite the fact that radiation risk communication occurs rarely, there is evidence to suggest that risk-benefit dialogue with patients could be a valuable tool for decreasing unnecessary CT use in an acute care setting. [27][28][29][30] A recent study revealed that most of the emergency department (ED) providers thought that the CT scans they ordered may have been unnecessary 25% to 50% of the time.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 99%